PEMBELAJARAN FISIKA MELALUI INKUIRI TERBIMBING DENGAN METODE EKSPERIMEN DAN DEMONSTRASI DITINJAU DARI AKTIVITAS DAN PERHATIAN MAHASISWA1) - Handhika, Jeffry (Jurnal Penelitian Pembelajaran Fisika, 2010)
The objective of the research are to know : (1) the effect of guided inquiryphysics learning using eksperiment and demonstration method to theconceptâs mastery in dynamic electricity, (2) the effect of high, medium andlow activity in physics learning to the conceptâs mastery in dynamicelectricity, (3) the effect of high, medium and low physics learning collagestudent attention in physics learning to the conceptâs mastery in dynamicelectricity, (4) interaction in physics learning between learning method andactivity to the conceptâs mastery in dynamic electricity, (5) interaction inphysics learning between learning method and physics learning collegestudent attention to the conceptâs mastery in dynamic electricity; (6)interaction in physics learning between activity and physics learning collagestudent attention to the conceptâs mastery in dynamic electricity, (7)interaction in physics learning between learning method, activity and physicslearning collage student attention to the conceptâs mastery in dynamicelectricity. The research is using experiment method. The technique ofanalyzing data is ANAVA three ways different cell. Based on the result of theresearch are concluded : (1) there is an effect of guided inquiry physicslearning using eksperiment and demonstration method to the conceptâsmastery in dynamic electricity, (2) there is an effect of high, medium and lowactivity in physics learning to the conceptâs mastery in dynamic electricity,(3) there is an effect of high, medium and low physics learning collagestudent attention in physics learning to the conceptâs mastery in dynamicelectricity, (4) there is no interaction in physics learning between learningmethod and activity to the conceptâs mastery in dynamic electricity, (5) thereis no interaction in physics learning between learning method and physicslearning second collage student attention to the conceptâs mastery indynamic electricity; (6) there is no interaction in physics learning betweenactivity and physics learning collage student attention to the conceptâsmastery in dynamic electricity, (7) there is no interaction in physics learningbetween learning method, activity and physics learning collage studentattention to the conceptâs mastery in dynamic electricity.